Coral reef aerosol emissions in response to irradiance stress in the Great Barrier Reef, Australia - Cropp, Roger (Ambio, 2018)
We investigate the correlation between stress-related compounds produced by corals of the Great Barrier Reef (GBR) and local atmospheric properties—an issue that goes to the core of the coral ecosystem’s ability to survive climate change. We relate the variability in a satellite decadal time series of fine-mode aerosol optical depth (AOD) to a coral stress metric, formulated as a function of irradiance, water clarity, and tide, at Heron Island in the southern GBR. We found that AOD was correlated with the coral stress metric, and the correlation increased at low wind speeds, when horizontal advection of air masses was low and the production of non-biogenic aerosols was minimal. We posit that coral reefs may be able to protect themselves from irradiance stress during calm weather by affecting the optical properties of the atmosphere and local incident solar radiation.